Antimicrobial and Radical Scavenging Activitıes of Essential Oils from Kaempferia larsenii Sirirugsa - Theanphong, Orawan; Mingvanish, Withawat; Jenjittikul, Thaya (Trends in Sciences, 2023)
Introduction: K. larsenii (Zingiberaceae) is an endemic and rare species in Thailand. There have been no previous reports on chemical compositions and biological properties of essential oils from the fresh root and rhizome. This research aims to investigate the chemical compositions, antimicrobial and radical scavenging activities of essential oils from the fresh root and rhizome of K. larsenii. Materials and methods: The chemical compositions of hydrodistilled essential oils were analysed by GC-MS technique. The antimicrobial activity was tested by the disc diffusion assay. The Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values were also evaluated. The radical scavenging activities were evaluated using ABTS, DPPH and hydroxyl radical scavenging activity assay. Results and discussion: Camphene was considered as the main component in root and rhizome essential oils (36.35 and 48.00 %, respectively). The essential oils showed strong antimicrobial activity against S. aureus. The rhizome essential oil showed strong DPPH and hydroxyl radical scavenging activities while the root essential oil exhibited strong hydroxyl radical scavenging capacity. Conclusions: The essential oils exhibit strong antimicrobial especially Gram-positive bacteria and antioxidant activity. Therefore, it might be used as a potential source of natural antidiarrheal and antioxidant substances for food and cosmeceutical product industries. HIGHLIGHTS The essential oils were obtained from hydrodistillation of the fresh root and rhizome of K. larsenii Camphene was the major component in both root and rhizome essential oils The root and rhizome essential oils showed strong antimicrobial on Gram-positive bacteria and radical scavenging activities This is the first report on the biological activities of the fresh root and rhizome essential oils of larsenii GRAPHICAL ABSTRACT